PWE-102 The use of TPMT Enzyme Testing in Managing Thiopurine Therapy. (4th June 2013) - Widlak, M; Smith, M; Slater, J; Wood, L; Silva, S De
Abstract : Introduction: Thiopurine methyl transferase (TPMT) enzyme deficiency is associated with azathioprine-induced myelosuppression and hepatotoxicity. We aimed to assess thiopurine methyl transferase levels (TPMT) in patients with inflammatory bowel disease (IBD) and to determine how these levels impact on thiopurine dosing and further treatment. Methods: Retrospective analysis of all adult IBD patients treated with azathioprine (AZA) who had TPMT levels checked in our department 2008 – 2012. Patient demographics, AZA dose, blood parameters, adverse effects and reason for discontinuation were recorded. Patients were treated to try and achieve a target dose of 2.0 – 2.5 mg/kg of AZA. Our laboratory enzyme assay defined normal TPMT level as 68–150 mU/L. Results: A cohort of 135 patients receiving azathioprine were identified. Mean age was 43 years (SD 17), M:F ratio 1:1. 72 patients (53%) had Crohn's disease, 60 (44%) ulcerative colitis and 3 (3%) indeterminate colitis. Mean starting dose of AZA 1.7 mg/kg (SD 0.6), maintenance dose 1.8 mg/kg (SD 0.5). 63 (47%) were initially dosed with ≥ 2.0 mg/kg. The mean TPMT level was 100 mU/L (SD 23); 14 patients (10%) had low levels. Patients with low TPMT levels were generally started at lower doses of AZA 1.3 mg/kg (SD 0.7) vs 1.8 mg/kg (SD 0.6). Mean length of follow up on AZA was 10.6 months (range 0.1 – 44). 50 out of 135 patients (37%) exhibited adverse effects during treatment (representing 44 of the 121 (36%) with normal TPMT levels, 6 of 14 (43%) with low TPMT). Median time to adverse effects was 3 months (range 0.1–22). Leucopenia developed in 11 (22%), deranged liver biochemistry 24 (48%), adverse symptoms 24 (48%). There was one case of pancreatitis and lymphoma respectively. Adverse effects were managed by discontinuation in 30 (60%), dose reduction 14 (28%), monitoring only 6 (12%). In the 6 patients with low TPMT levels, 4 developed deranged liver biochemistry and 2 had leucopenia; in 50% AZA was discontinued. The median time to adverse effects was 11 months (range 2–22), with 5 out of 6 patients developing adverse effects after more than 6 months of treatment. Conclusion: In our cohort low TPMT enzyme activity was not associated with an early onset of adverse effects or an excess of adverse effects when compared to the normal TPMT group. We would suggest that the value of TPMT level testing prior to thiopurine therapy may be less of a priority than vigilant monitoring of blood parameters during AZA therapy in identifying serious adverse effects. Disclosure of Interest: None Declared.